Pemanfaatan Gulma Supan-Supan (Neptunia oleracea L.) Sebagai Pupuk Organik Plus Agens Hayati Untuk Mengendalikan Nematoda Meloidogyne spp. Pada Tanaman Seledri (Apium graveolens L.) - Nafisa, Lingzhi Zilfa; Liestiany, Elly; Rosa, Helda Orbani (www.ulm.ac.id, 2025)
Celery is a vegetable that plays an important role in meeting the nutritional needs of Indonesian people. However, celery production faces several challenges, including root knot disease caused by the nematode Meloidogyne spp. This causes a significant decrease in productivity. The biological control used is environmentally friendly biological control using Bokashi fertilizer using Supan-supan weed (Neptunia oleracea L.), EM4, PGPR and a mixture of EM4 as a decomposer with the addition of Trichoderma sp. The aim of this research is to determine the potential of supan-supan weed as an organic fertilizer together with the biological agent Trichoderma sp. in controlling root nematodes Meloidogyne spp. on celery plants. The research was carried out from January to July 2024 in Sungai Besar Village and the Phytopathology Laboratory, Faculty of Agriculture, Lambung Mangkurat University, Banjarbaru. The research method used a completely randomized design (CRD) using the test agents EM4, PGPR, Ecoenzyme and Trichoderma sp. which consisted of (7) treatments with (4) replications and each experimental unit consisted of (3) plants so that the total plants were 84 plants. The results showed that giving EM4, PGPR and eco-enzyme could decompose bokashi supan-supan fertilizer and giving bokashi supan-supan + EM4 + Trichoderma sp. is the best treatment for the number and severity of root knot nematodes.